The effects of tourism e-commerce live streaming features on consumer purchase intention: The mediating roles of flow experience and trust - Liu, Xiaoli; Zhang, Lei; Chen, Qian (Frontiers in Psychology, 2022)
Given that tourism e-commerce live streaming has become an important driver of tourism development after the outbreak of Covid-19 but limited attention has been paid to this area，this study examines the impacts of tourism e-commerce live streaming features (interactivity, authenticity , and entertainment) on the consumers' purchase intention from the perspectives of consumers' flow experience and trust based on the SOR theory. The authors collected survey data from 357 tourism e-commerce live streaming consumers and used the structural equation model to test the research model. The results reveal that interactivity and authenticity positively affect tourism e-commerce live streaming consumers' purchase intention，but entertainment does not influence purchase intention positively; interactivity, authenticity , and entertainment each positively affects tourism e-commerce live streaming consumers' flow experience and trust; both flow experience and trust positively affect tourism e-commerce live streaming consumers' purchase intention; both flow experience and trust have mediating effects on the relationships between tourism e-commerce live streaming features and consumers' purchase intention. This study extends existing theoretical research on tourism e-commerce live streaming and provides some managerial implications for tourism enterprises and streamers.